Antimicrobial resistance in E. coli isolated from dairy calves and bedding material. Issue 11 (November 2019) - Astorga, Francisco; Navarrete-Talloni, María J.; Miró, María P.; Bravo, Verónica; Toro, Magaly; Blondel, Carlos J.; Hervé-Claude, Luis P.
Abstract: Introduction: E. coli is a ubiquitous bacterium commonly used as a sentinel in antimicrobial resistance studies. Here, E. coli was isolated from three groups (sick calves, healthy calves and bedding material), to assess the presence of antimicrobial resistance, describe resistance profiles, and compare these resistances among groups. Material and methods: Samples were collected from calves and calving pens from 20 dairy farms. Using the disc diffusion method, E. coli isolates were screened for antimicrobial resistance against seven antimicrobials: Amoxicillin, Ceftiofur, Gentamicin, Enrofloxacin, Trimethoprim–sulfamethoxazole, Florfenicol and Oxytetracycline. Isolates resistant to all these seven antimicrobials were tested again against an extended 19 antimicrobial drug panel and for the presence of the most common E. coli pathogenicity genes through PCR. Results & discussion: Three hundred forty-nine E. coli isolates were obtained; most isolates were resistant to a single antimicrobial, but 2.3% (8) were resistant to 16 to 19 of the antimicrobials tested. The group with the highest percentage of multiresistant isolates was the calves with diarrhea group. Younger calves provided samples with higher antimicrobial resistance levels. Conclusions: There is a high rate of antimicrobial resistance in dairy farms calving pens. These bacteria could not only be a resistance gene reservoir, but also could have the potential to spread these determinants through horizontal gene transfer to other susceptible bacteria. Measures should be taken to protect colonization of younger calves, based on hygienic measures and proper management. Abstract : Agriculture; Microbiology; Animal science; Cattle; Livestock management; Veterinary medicine; Animal breeding; Ruminant; Antimicrobial resistance; Dairy; E. coli ; Calf.